Dispensing pleasantries? Responding to legitimacy and reputation in online medical marijuana marketing. Issue 8 (19th September 2016) - Washburn, Mark; Klein, Kenji
Abstract : Purpose: The purpose of this paper is to develop theory regarding reputation and legitimacy signaling by organizations in contested emerging fields characterized by category ambiguity. Because impression management becomes increasingly important as category boundaries become fuzzy, the authors examine how highly participatory audiences in contested emerging fields respond to organizational attempts to seek acceptance and manage impressions. Design/methodology/approach: Using a database of web-based advertisements by 1, 226 medical marijuana dispensaries, the authors test the effect that dispensary attempts to signal either legitimacy or reputation have on audience approval. Findings: The authors find that audiences react differently to communication strategies intended to build reputation vs those intended to build legitimacy. Under conditions of highly contested category legitimation, audiences respond positively to signals of legitimacy but negatively to signals of reputation. Originality/value: This study advances the understanding of category emergence and category building under conditions of contestation. The study adds to the growing body of work that suggests category creation involves unique collaborative processes between organizations and audiences, and the authors show that these processes constrain organizational attempts at impression management.